2017
DOI: 10.4025/actascitechnol.v39i5.29723
|View full text |Cite
|
Sign up to set email alerts
|

<b>Formulation of fish waste meal for human nutrition

Abstract: ABSTRACT. This study aimed to elaborate and characterize meals containing waste from processing of tilapia, tuna, salmon and sardine for human consumption. Carcasses of tilapia and salmon, tuna torsos without fins and sardine tails were cooked, pressed, milled and dehydrated, resulting in waste meal. Greater protein (83.28%) and lower mineral matter (5.31%) were observed in tuna meal. Salmon meal presented greater content of lipids (18.81%) and sardine meal, lower content (3.98%). Tilapia meal presented greate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
11

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 26 publications
2
21
0
11
Order By: Relevance
“…These values indicate that the mix is a protein food with high content of lipids and ash, similar to the values reported by Souza et al (2016) for tilapia, tuna, salmon and sardine meals.…”
Section: Chemical Composition and Calorific Valuesupporting
confidence: 73%
“…These values indicate that the mix is a protein food with high content of lipids and ash, similar to the values reported by Souza et al (2016) for tilapia, tuna, salmon and sardine meals.…”
Section: Chemical Composition and Calorific Valuesupporting
confidence: 73%
“…These authors identified 24 fatty acids in flour with primarily the following fatty acids: 27.4% of palmitic acid (C16:0), 35.15% of oleic acid (C18:1n-9), 11.82% of linoleic acid (C18:2n-6), and in a lower proportion: 0.88% of alpha-linolenic acid (C18:3n-3), 0.08% of eicosapentanoic acid (C20:5n-3), and 0.59% of docosahexaenoic acid (C22:6n-3) (Petenuci et al, 2010). No presented data regarding tilapia protein concentrate used to prepare noodles in this study presented 21.16% of polyunsaturated fatty acids (PUFA) in tilapia protein concentrate which 4.28% are omega-3 and 12.26% are omega-6 (Souza et al, 2016).…”
Section: Resultsmentioning
confidence: 73%
“…It is worth noting that the protein quality of the noodles with protein concentrate is greater than others, because fish and their derivatives contain a high biologic protein with a balanced amino acid profile and a good proportion of methionine and cysteine, which are the main limiting amino acids in vegetal protein sources (Neves et al, 2004). Previous studies evaluating the amino acid composition in tilapia protein concentrate (Souza et al, 2016) showed that protein concentrate also contains all essential amino acids, and that the amino acid content is much greater than the standard required by the FAD (Food and Agriculture Drganization of the United Nations) for both children and adults (World Health Drganization, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Ween et al (2017) reported fish meal processed from fresh by-products of whitefish such as cod and saithe was a tremendous protein source with the presence of all nutritionally EAA and low content of free amino acids (0.7%) and biogenic amines (< 1000 mg/kg) that approve the high quality and freshness of the natural resource. Similarly, Souza et al (2017) reported that fish waste meal originated from various kinds of fish including tilapia, tuna, salmon, and sardine had better proportion of glutamic acid, lysine, leucine, glycine, and aspartic acid. According to Cho and Kim (2011), fish meal and fish oils (FO) are major dietary sources of n-3 long-chain polyunsaturated fatty acids (PUFA), docosahexaenoic acid (22:6n-3), and eicosapentaenoic acid (20:5n-3).…”
Section: Yolk Indexmentioning
confidence: 94%